2010
DOI: 10.2353/ajpath.2010.091164
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response-1 Induces and Enhances Vascular Endothelial Growth Factor-A Expression in Lung Cancer Cells

Abstract: Vascular endothelial growth factor-A (VEGF-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 53 publications
3
54
0
1
Order By: Relevance
“…In an effort to better understand the mechanisms responsible for these cellular responses, we measured the expression of Egr-1 protein and found that TGZ stimulates the expression of Egr-1 in a concentrationdependent manner. Egr-1 is a member of the immediate early gene response family and encodes a nuclear phosphoprotein involved in the regulation of cell growth and differentiation in response to signals such as mitogens, growth factors and stress stimuli (19)(20)(21). However, evidence suggests that Egr-1 binding sites are located within region -73 to -51 of the NAG-1 promoter, and the overexpression of Egr-1 results in increased NGA-1 expression.…”
Section: Discussionmentioning
confidence: 97%
“…In an effort to better understand the mechanisms responsible for these cellular responses, we measured the expression of Egr-1 protein and found that TGZ stimulates the expression of Egr-1 in a concentrationdependent manner. Egr-1 is a member of the immediate early gene response family and encodes a nuclear phosphoprotein involved in the regulation of cell growth and differentiation in response to signals such as mitogens, growth factors and stress stimuli (19)(20)(21). However, evidence suggests that Egr-1 binding sites are located within region -73 to -51 of the NAG-1 promoter, and the overexpression of Egr-1 results in increased NGA-1 expression.…”
Section: Discussionmentioning
confidence: 97%
“…[26][27][28][29][30][31] H1688, H441, and A549 were purchased from the American Type Culture Collection (ATCC, Manassas, VA, USA), and LC2/ad was obtained from the Riken Bioresource Center (Ibaraki, Japan). Non-small-cell lung cancer (NSCLC) cells were cultivated in Dulbecco's modified Eagle's medium, and SCLC cells were cultured in RPMI-1640 medium.…”
Section: Materials and Methods Cultured Lung Cancer Cellsmentioning
confidence: 99%
“…26 The equivalent volume of vehicle, 50% acetic acid for AZA (VCL1) or 100% ethanol for TSA (VCL2), was applied as a control.…”
Section: Bisulfite Sequencingmentioning
confidence: 99%
“…14,15 The association between Egr-1 and tumor angiogenesis has been observed in various tumor types. [16][17][18] A DNA-based enzyme and a siRNA that target Egr-1 suppress bFGF expression and tumor angiogenesis and growth in various cancer cell types. [18][19][20][21] In this study, we determined the mechanisms by which IGFBP-3 exerts its IGF-independent antiangiogenic antitumor activity.…”
Section: Introductionmentioning
confidence: 99%